Peningkatan Kualitas Sari Buah Naga Super Red (Hylocereus Costaricencis) Melalui Introduksi Teknik Ekstrasi dan Aplikasi Enzim Pektinase di Desa Krikilan, Masaran, Sragen, Jawa Tengah - Esti Widowati; Bambang Sigit Amanto (PRIMA: Journal of Community Empowering and Services, 2019)
Title:Improving the Quality of Super Red Dragon Fruit (Hylocereus Costaricencis) Through the Introduction of Extraction Techniques and Application of Pectinase Enzyme in Krikilan Village, Masaran, Sragen, Central Java. This activity was a collaboration with the Wana Bekti Farmers Group and Wana Bekti Handayani Small Medium Enterprise (SME) in Masaran Sragen, Central Java. They have problem with super red dragon fruit juice products. They need technology to improve the quality of juice that tends to separate during storage even though it has been through a screening process. The selling power of this product was low and not became the main product of Wana Bekti Handayani SME because the consumers consider this product unfit for consumption if visually separated. Therefore, as an applicable solution to this problem, this activity introduces the extraction technology and the application of the enzyme pectinase, namely polygallacturonase 0.1% which able to clarify the juice so it can maintain the texture of the juice looks homogeneous. The direct impact was the increasing of the quality of the juice products,  thereby increasing the selling power of the product.